FAKTOR-FAKTOR PENYEBAB KEMATIAN BAHASA - IRWAN IRWAN (Ta'dib, 2011)
This article discusses about the factors which may cause language death or language dissappear.  Based on some linguists’ research there are several factors that might cause the death of the language.  They are: natural disaster, war and ethnic clearance, epidemic sickness, hegemony of a foreign language, inferior of language sense, migration, political decision, and intercultural marriage problem.  In this article the writer would like to anlayze each point of the factors above.  The conclusion is a language is like other human life; born, live, develop, lying up and death.  This phenomenon is called survival of the fittest; the majority language will hit the minority language along its life.Kata kunci:  faktor, kematian, bahasa, dissappear